Safety and efficacy of Hemicell®‐L (endo‐1, 4‐β‐mannanase) as a feed additive for chickens for fattening or reared for laying, turkeys for fattening or reared for breeding and minor poultry species. (1st April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive Hemicell ® ‐L is a liquid preparation of endo‐1, 4‐β‐mannanase that is authorised as a zootechnical feed additive for chickens for fattening. The applicant has requested the renewal of the authorisation, new uses and the modification of the manufacturing process including the change of the production strain. The new production strain is a genetically modified strain of Paenibacillus lentus obtained from a strain that has been evaluated previously by EFSA and considered to be safe. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) evaluated the genetic modification and concluded that the sequences introduced to obtain the production strain did not raise safety concerns. The production strain and its DNA were not detected in the additive. The Panel concluded that the additive is safe for chickens for fattening and turkeys for fattening at the recommended level. These conclusions were extended or extrapolated to the other target species under application. The Panel concluded that the results obtained in the toxicological studies performed with the fermentation products of the recipient strain and of another genetically modified strain obtained from the same recipient strain could support the safety for the consumer of the product obtained with the new production strain. The additive is not a dermal or eye irritant and it is not a dermal sensitiser. However, considering that the active substance is a protein, the additive should be regarded as a potential sensitiser. The Panel concluded that the additive has a potential to be efficacious as a zootechnical additive for the target species at 79, 200 U/kg.